2021
DOI: 10.3389/fimmu.2021.642087
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of the Detection of the Loss of the Mismatched HLA in Relapsed Hematological Patients After Haploidentical Stem Cell Transplantation With High-Dose Cyclophosphamide

Abstract: Haploidentical hematopoietic stem cell transplantation (Haplo-HSCT) with high-dose cyclophosphamide (PTCy) has resulted in a low incidence of graft-vs.-host disease (GVHD), graft failure, and non-relapse mortality. However, post-transplantation relapse remains a common cause of treatment failure in high-risk patients. Unraveling the mechanisms of relapse is therefore crucial for designing effective relapse treatment strategies. One of these mechanisms is the loss of the mismatched HLA on the recipient's leukem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
2
1
5
Order By: Relevance
“…Unlike previous studies of myeloid conditions, 12,26 we found that the pretransplant BMI of patients was associated with HLA loss; patients with lower BMI were less likely to lose unshared HLA at relapse. A previous study 30 found that underweight patients had a higher rate of posttreatment relapse, which suggests underweight status could reflect the biological aggressiveness of leukemia.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Unlike previous studies of myeloid conditions, 12,26 we found that the pretransplant BMI of patients was associated with HLA loss; patients with lower BMI were less likely to lose unshared HLA at relapse. A previous study 30 found that underweight patients had a higher rate of posttreatment relapse, which suggests underweight status could reflect the biological aggressiveness of leukemia.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of the present study suggested that male patients with lymphoid leukemia were less likely to have HLA loss at relapse, which was consistent with the findings of a recent study. 26 Although sex is associated with many autoimmune disorders, the difference in immune regulation based on sex is unclear. One study 27 found that sex can have implications for the selection and expansion of HLA-associated T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…При острых лейкозах рецидив с потерей HLA происходит позже, чем классический вариант реци-дива [21,22]. В предыдущей работе нашего научного коллектива медиана развития рецидива с потерей HLA у детей с острыми лейкозами составила 8 мес [11].…”
Section: обсуждение результатов исследованияunclassified
“…В качестве факторов риска, ассоциированных с потерей по генам HLA, могут выступать неблагоприятная цитогенетика, ABO-несовместимость, активное заболевание на момент алло-ТГСК, развитие острой и хронической РТПХ [11,21,22]. Биология лейкоза, отсутствие ремиссии перед алло-ТГСК, а также развитие РТПХ могли способствовать клональной эволюции опухоли после алло-ТГСК с последующей потерей HLA-гаплотипа.…”
Section: обсуждение результатов исследованияunclassified